Hubungan Efikasi Diri Dengan Kecemasan Akademik Pada Mahasiswa Baru Fakultas Keperawatan Universitas Padjadjaran - Namina, Fajaritta Sukma; Mediawati, Ati Surya; Kosim, Kosim (Jurnal Ilmiah Global Education, 2025)
Academic anxiety remains a common issue among first-year nursing students. This condition can be minimized by increasing self-confidence with self-efficacy playing a protective role. This study aims to analyze the relationship between self-efficacy and academic anxiety among first-year students at the Faculty of Nursing, University of Padjadjaran. A quantitative approach was employed using a correlational design with a cross-sectional method. The study population consisted of 239 students from the 2024 cohort at the Jatinangor and Pangandaran campuses, with a sample of 150 students selected using the Sloving formula and cluster random sampling. The instrumens used were the General Self-Efficacy Scale and the Academic Anxiety Scale, both of which have been proven valid and reliable in previous studies. The results indicate that the average self-efficacy score was in the moderate category (29,87) and the average academic anxiety score was in the high category (122,30), with a significant negative correlation between self-efficacy and academic anxiety (p=0.000; p<0,05; r=-0.308). the study concludes that increasing students self-efficacy may help reduce the level of academic anxiety among first-year nursing students.